Spectrophotometric and Potentiometric Analysis of Calcichrome and Its Complex With Calcium Ion - Al-Samarra’ay, Saja S; Al-Hitti, Ismail K; Al-oubaydi, Omur H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
It was confirmed in this research that the ligand calcichrome formed stable complex with calcium ion at pH of  8.5 which verified by UV/Vis and FTIR spectral analysis and the complexation occurred via hydroxyl groups .The stoichiometric ratio of the formed complex was found to be 1:1 by mole ratio and continuous variation methods . Dry ashing method of the complex and flame emission photometric analysis offered a calcium percentage in calcium complex equal 4.5% with an error of 2.41% due to experimental errors .